Концепти сім’я, шлюб в архаїчній народопісенній творчості українців - Павлушенко, Ольга; Мазай, Лада (Slavia Orientalis, 2026)
The proposed research is based on the general academic principle of linguistics, according to which linguistic phenomena are particularly interesting from the perspective of ethno‑ and mental‑linguistic studies. The research goal is a linguistic analysis of the linguistic constructs and mental concepts of family and marriage in the Ukrainian ethnomentality, conducted through the lens of the oldest ethnographic texts. The empirical basis for the research was archaic texts – primarily Christmas carols, shchedrivkas, and other ritual songs – collected and published in the unique anthology «Золотослов. Поетичний космос Давньої Русі» (‘Zolotoslov. The Poetic Cosmos of Ancient Rus’) and in the collection «Календарні пісні Великої Волині. Збірник народних пісень» (‘Calendar Songs of Great Volhynia. A Collection of Folk Songs’). The use of conceptual analysis allowed us to identify the established meanings of the concepts studied, which determine the ethnocultural traditions of Ukrainians as they perceive them: the importance of family for the existence and life activity of society as a whole, the status of women and the role of men in the family, the relationship between parents and children, the foundations of family well‑being, and the moral and ethical norms of married life. An analysis of the texts of Ukrainian folk songs allows us to conclude that a characteristic feature of the Ukrainian family in ancient times was a tendency towards matriarchal forms. The man – the father – never subordinated family life to himself, while the woman – the mother – was always the centre of attention. This, in turn, due to the monogamous nature of women, favoured the perpetuation of monogamous family forms. The study also included an analysis of the conceptual meanings of the original symbolism of Ukrainian folk songs.